Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Usaha Bubur Ibu Masudah - Faizah Azzahra; Alinudin Alinudin; Riki Gana Suyatna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development of the business world has increased rapidly in the modern era like today. This causes intense competition between business actors in developing their products in the face of developments in the business world. Micro, small and medium enterprises or MSMEs now play a very important role in the growth of the economy in Indonesia. Mrs. Maubah's porridge business is one of the MSMEs in Cilegon City, Banten which operates in the food sector. This business can provide jobs for the local community. My mother's porridge business itself is a type of food business which sells various variations of porridge and various other fried foods. This research aims to find out what marketing strategies are implemented by Ibu Majadi's porridge business to increase sales. Carrying out a SWOT (Strength, Weakness, Opportunity, and Threat) analysis in determining the marketing strategy. This research is included in qualitative descriptive research, because it aims to describe the situation of phenomena in the field. Researchers used data collection methods in research, namely observation and interviews. To find out how the strategy is used, the Swot Analysis Method (Strength, Weakness, Opportunity and Threat). From the results of the SWOT analysis, it was concluded that the results of the IFAS (Internal Factor Analysis Summary), for the strength and weakness variables, each obtained a strength value of 1.89, while a value of 1.00 was obtained for weaknesses. This means that the strengths of Mrs. Matahu's porridge business are greater than the weaknesses. Meanwhile, the value obtained for the EFAS (External Factor Analysis Strategy) Matrix was 1.47 for opportunities, while the value for threats was 0.64. This means that for Mrs. Matahu's porridge business, the opportunity value is greater than the threat value. From the results of the SWOT analysis, it was found that Ibu Ma's porridge business has strengths and opportunities so that it will be able to take advantage of existing opportunities. The strategy that must be implemented in this condition is to support the policy of growing aggression.